PENGETAHUAN DAN SIKAP REMAJA PUTRI SMA MENGENAI PERINEAL HYGIENE DENGAN TERJADINYA KEPUTIHAN - Maisyeliani Anggelita Baureh; Grace Fresania Kaparang; Lea Andy Shintya (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2022)
Various problems such as vaginal discharge, cervical cancer, skin irritation, genitals, allergies, inflammation or urinary tract infections may arise if poor maintenance over the cleanliness of the reproductive organs. Therefore, it is essential to have good knowledge and attitude regarding perineal hygiene to achieve reproductive health for adolescents. This study is to find out the relationship of knowledge and perineal hygiene attitudes, and the incidence of female adolescent vaginal discharge and whether there is a relationship between knowledge and perineal attitudes of adolescent hygiene towards the occurrence of vaginal discharge at U High School in Airmadidi. This study is a correlation study with consecutive sampling techniques. The results showed that of the 57 participants, 87.7% had received information about perineal hygiene and 50.9% got information from the internet. It was also found that 71.9% of students were at low knowledge levels but 82.5% had a good attitude, while the incidence of vaginal discharge was found at 96.5%. The spearman test found that there was a relationship of perineal hygiene knowledge with the incidence of vaginal discharge with p = 0.039<.05 with a value of r = 0.274 (weak positive strength), and there was no relationship between perineal hygiene attitude and the occurrence of vaginal discharge where p = 0.142 > 0.05. Recommendations for the next study to include other variables. For the school, to facilitate information in order to increase students' knowledge about perineal hygiene and the dangers of vaginal discharge if not handled properly.